Getting price right : the behavioral economics of profitable pricing - Smith, Gerald, 1953- (New York : Columbia University Press, 2021)
"Managerial pricing decisions lead to surprisingly counterintuitive-seemingly irrational-behaviors, often contradicting what traditional economics predicts. However, sometimes these misunderstood behaviors are in fact more rational than they appear. How do leaders, managers, and proprietors go about the essential task of setting prices? What biases enter into this process, and why? How can a business remove biases from its price setting to become more productive, strategic, and profitable? Combining perceptive insights from behavioral economics with leading-edge ideas on price management, this book offers a new approach to pricing. Gerald Smith demonstrates why understanding, reframing, and refining everyday pricing processes-one's pricing orientation-results in a better long-term pricing strategy. He explores how pricing actually happens in practice and shows how to identify and remove the psychological blinders that cause suboptimal decisions and policies. Smith details how to improve pricing orientation by combining the soft behavioral skills that intuitively shape and refine practice with the hard analytic skills that guide and structure pricing strategy. The result is more rational and more profitable pricing-with respect not only to revenue but also employee productivity and customer satisfaction. Offering an accessible and actionable model, Getting Price Right is the first book to apply behavioral economics to managerial price setting. It is a must-read for business leaders, thought leaders, and professionals interested in advances in pricing and for managers, entrepreneurs, proprietors, and small and midsize business owners whose everyday work involves pricing"--
Part I. Behavioral economics of everyday pricing decisions. Pricing orientation, pricing strategy -- Framing and strategic frames of reference -- Psychological pricing orientation : psychological price-setting biases and skills -- Social pricing orientation : cultural price-setting biases and skills -- Part II. Behavioral economics of cardinal pricing orientations. Cost-driven pricing orientation biases and skills -- Customer value-driven pricing orientation biases and skills -- Customer willingness-to-pay-driven pricing orientation biases and skills -- Competition-driven pricing orientation biases and skills -- Balanced pricing orientations, profitable pricing strategy.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 02, 2021).
JSTOR
Keywords: Pricing; Economics -- Psychological aspects; Price fixing; Prix -- Fixation; Économie politique -- Aspect psychologique; BUSINESS & ECONOMICS / Consumer Behavior; Price fixing; Economics -- Psychological aspects; Pricing